2023
DOI: 10.3389/fonc.2023.1155621
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic changes underlying drug resistance in the multiple myeloma tumor microenvironment

Abstract: Multiple myeloma (MM) is characterized by the clonal expansion of malignant plasma cells in the bone marrow (BM). MM remains an incurable disease, with the majority of patients experiencing multiple relapses from different drugs. The MM tumor microenvironment (TME) and in particular bone-marrow stromal cells (BMSCs) play a crucial role in the development of drug resistance. Metabolic reprogramming is emerging as a hallmark of cancer that can potentially be exploited for cancer treatment. Recent studies show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 140 publications
0
1
0
Order By: Relevance
“…2C), providing information on pathway dynamics in cell populations (Table 1). Stable isotope tracing has been pivotal in studying pathway dynamics and understanding metabolic switches in many immune cell types [98][99][100][101][102][103][104][105]. For example, Mensink et al [100] recently performed tracing experiments using 13 C 6 -glucose and 13 C 5 -glutamine to determine the effect of tumor necrosis factor receptor 2 (TNRF2) co-stimulation on CD4 + conventional and regulatory T cells.…”
Section: Advances In Stable Isotope Tracing To Map Metabolic Reaction...mentioning
confidence: 99%
See 3 more Smart Citations
“…2C), providing information on pathway dynamics in cell populations (Table 1). Stable isotope tracing has been pivotal in studying pathway dynamics and understanding metabolic switches in many immune cell types [98][99][100][101][102][103][104][105]. For example, Mensink et al [100] recently performed tracing experiments using 13 C 6 -glucose and 13 C 5 -glutamine to determine the effect of tumor necrosis factor receptor 2 (TNRF2) co-stimulation on CD4 + conventional and regulatory T cells.…”
Section: Advances In Stable Isotope Tracing To Map Metabolic Reaction...mentioning
confidence: 99%
“…Using this system, the authors found that cytokines (IL-6) and chemokines (CCL5, CXCL10) secreted by cancer-associated fibroblasts induce glycogen breakdown in ovarian cancer cells to promote proliferation and invasion [106]. Using 13 C 6glucose tracing in combination with a Transwell coculture system, Matamala Montoya et al [101] recently demonstrated the importance of bone-marrow stromal cells in inducing drug resistance-associated metabolic rewiring in multiple myeloma. To map cell-type-specific dynamic changes in central carbon metabolism, Wang et al [107] applied an advanced high-spatial-resolution metabolomics approach using MALDI-MSI combined with isotope tracing in an organoid co-culture.…”
Section: Advances In Stable Isotope Tracing To Map Metabolic Reaction...mentioning
confidence: 99%
See 2 more Smart Citations
“…Mitochondrial alterations, with increased biomass as well as unbalanced mitochondrial functions, can prompt metabolic changes which have been found instrumental in MM onset and chemoresistance [ 6 , 16 , 17 ]. MM cells are strictly dependent on glucose metabolism by enhancing glucose uptake and aerobic glycolysis and producing lactate, providing an important carbon source for tricarboxylic acid (TCA) cycle and OXPHOS, required to maintain elevated protein synthesis, folding and secretion.…”
Section: Introductionmentioning
confidence: 99%